2018
DOI: 10.3747/pdi.2018.00115
|View full text |Cite
|
Sign up to set email alerts
|

Brucella Peritonitis in a Patient on Peritoneal Dialysis: Case Report and Literature Review

Abstract: Peritonitis is the most common complication in patients undergoing peritoneal dialysis (PD). Peritoneal dialysis-related peritonitis caused by Brucella species has been reported in only 7 patients before. Here, we report a further case of Brucella peritonitis. This patient was successfully treated with both intraperitoneal and prolonged oral antibiotics, without removal of the PD catheter. We review relevant literature and make recommendations for the diagnosis and treatment of Brucella PD-related peritonitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
1
8
0
7
Order By: Relevance
“…However, our patient was successfully treated with antibiotics without the removal of the PD catheter. Niu et al suggested that catheter removal should be considered for those patients with severe manifestations, who are unresponsive despite optimal treatment with intraperitoneal antibiotics and appropriate oral antibiotics [ 16 ]. Several studies have shown that it is necessary to use antibiotics for at least six weeks or more to avoid relapse or develop resistance [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our patient was successfully treated with antibiotics without the removal of the PD catheter. Niu et al suggested that catheter removal should be considered for those patients with severe manifestations, who are unresponsive despite optimal treatment with intraperitoneal antibiotics and appropriate oral antibiotics [ 16 ]. Several studies have shown that it is necessary to use antibiotics for at least six weeks or more to avoid relapse or develop resistance [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that it is necessary to use antibiotics for at least six weeks or more to avoid relapse or develop resistance [ 6 ]. The best results are observed when antimicrobial treatment is administered early in combination therapy with adequate dosing [ 16 ]. The treatment commonly used for children is age-specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case represents a probable endometrioma sub infection, noting that the patient presented a 4.2 cm endometrioma on a previous ultrasound. To our knowledge, 8 cases of documented acute peritonitis due to brucella infection [ 18 ], and 2 cases of dermoid cyst subinfection were found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Huiping Zhao et. al., worked on the concept of intraperitoneal method and the prolonged oral antibodies technique to treat the patients with peritonitis [7]. Brucollis is caused by the brucella.…”
Section: Paper Surveymentioning
confidence: 99%